Mesenchymal Stem Cells: Allogeneic MSC May Be Immunosuppressive but Autologous MSC Are Dysfunctional in Lupus Patients - Cheng, Rui-Juan; Xiong, An-Ji; Li, Yan-Hong; Pan, Shu-Yue; Zhang, Qiu-Ping; Zhao, Yi; Liu, Yi; Marion, Tony N. (Frontiers in Cell and Developmental Biology, 2019)
Mesenchymal stem cells (MSCs) have a potently immunosuppressive capacity in both innate and adaptive immune responses. Consequently, MSCs transplantation has emerged as a potential beneficial therapy for autoimmune diseases even though the mechanisms underlying the immunomodulatory activity of MSCs is incompletely understood. Transplanted MSCs from healthy individuals with no known history of autoimmune disease are immunosuppressive in systemic lupus erythematosus (SLE) patients and can ameliorate SLE disease symptoms in those same patients. In contrast, autologous MSCs from SLE patients are not immunosuppressive and do not ameliorate disease symptoms. Recent studies have shown that MSCs from SLE patients are dysfunctional in both proliferation and immunoregulation and phenotypically senescent. The senescent phenotype has been attributed to multiple genes and signaling pathways. In this review, we focus on the possible mechanisms for the defective phenotype and function of MSCs from SLE patients and summarize recent research on MSCs in autoimmune diseases.